2011
DOI: 10.1371/journal.pone.0028499
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Downregulation of Matrix Metalloproteinase-9 in Rat Glial Cells by CCR5 Antagonist Maraviroc: Therapeutic Implication for HIV Brain Infection

Abstract: BackgroundMatrix metalloproteinases (MMPs) released by glial cells are important mediators of neuroinflammation and neurologic damage in HIV infection. The use of antiretroviral drugs able to combat the detrimental effect of chronic inflammation and target the exaggerated MMP activity might represent an attractive therapeutic challenge. Recent studies suggest that CCR5 antagonist maraviroc (MVC) exerts immunomodulant and anti-inflammatory activity beyond its anti-HIV properties. We investigated the in vitro ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…MMP9 knockout reduces neuro-inflammation in experimental autoimmune encephalomyelitis (EAE) [11], while CSF MMP9 is elevated in patients with bacterial meningitis and BBB damage [12]. Moreover, inhibition of MMP9 alleviates the neurological damage associated with human immunodeficiency virus (HIV) infection [13], suggesting that MMP9 activation is a response to HIV infection. These data are also supported by enhanced expression and activity of MMP9 in serum, CSF, and demyelinating lesions in MS [14], and abundant evidence of increased MMP9 expression and activity in ischemic stroke [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…MMP9 knockout reduces neuro-inflammation in experimental autoimmune encephalomyelitis (EAE) [11], while CSF MMP9 is elevated in patients with bacterial meningitis and BBB damage [12]. Moreover, inhibition of MMP9 alleviates the neurological damage associated with human immunodeficiency virus (HIV) infection [13], suggesting that MMP9 activation is a response to HIV infection. These data are also supported by enhanced expression and activity of MMP9 in serum, CSF, and demyelinating lesions in MS [14], and abundant evidence of increased MMP9 expression and activity in ischemic stroke [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…In chronic inflammation, all MMPs may be present (Ra and Parks, 2007). In vitro findings indicate MMP changes in response to antiretrovirals (Gramegna et al , 2011; Latronico et al , 2007), suggesting that MMPs may represent potential therapeutic targets. However, evidence of MMP physiologic significance in cognitive function underscores the necessity of further studies before MMPs are targeted for clinical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to human immunodeficiency virus (HIV) infection, Gramegna et al . () found that the inhibition of MMP‐9 alleviated HIV‐associated neurological damage. Interestingly, Rumbaugh et al .…”
Section: Pathologies: Predisposition Diagnosis and Therapy (Animal mentioning
confidence: 98%